The economic impact of sight loss and blindness in the UK adult population - Lynne Pezzullo; Jared Streatfeild; Philippa Simkiss; Darren Shickle (BMC, 2018)
Abstract Background To quantify the economic impact of sight loss and blindness in the United Kingdom (UK) population, including direct and indirect costs, and its burden on health. Methods Prevalence data on sight loss and blindness by condition, Census demographic data, data on indirect costs, and healthcare cost databases were used. Blindness was defined as best corrected visual acuity (BCVA) of < 6/60, and sight loss as BCVA < 6/12 to 6/60, in the better-seeing eye. Results Sight loss and blindness from age-related macular degeneration (AMD), cataract, diabetic retinopathy, glaucoma and under-corrected refractive error are estimated to affect 1.93 (1.58 to 2.31) million people in the UK. Direct health care system costs were £3.0 billion, with inpatient and day care costs comprising £735 million (24.6%) and outpatient costs comprising £771 million (25.8%). Indirect costs amounted to £5.65 (5.12 to 6.22) billion. The value of the loss of healthy life associated with sight loss and blindness was estimated to be £19.5 (15.9 to 23.3) billion or £7.2 (5.9 to 8.6) billion, depending on the set of disability weights used. For comparison with other published results using 2004 disability weights and the 2008 estimates, the total economic cost of sight loss and blindness was estimated to be £28.1 (24.0 to 32.5) billion in 2013. Using 2010 disability weights, the estimated economic cost of sight loss and blindness was estimated to be £15.8 (13.5 to 18.3) billion in 2013. Conclusions The large prevalence of sight loss and blindness in the UK population imposes significant costs on public funds, private expenditure, and health. Prevalence estimates relied on dated epidemiological studies and may not capture recent advances in treatment, highlighting the need for population-based studies that track the prevalence of sight-impairing eye conditions and treatment effects over time.